SURGICAL TREATMENT METHODS FOR CARPAAL TUNAL STENOSIS (World Bulletin of Public Health, 2024)
We have observed 60 patients with carpal tunnel stenosis since 2015. until 2022 , surgical treatment in the emergency traumatology department of the Russian Research Center for Medical Physics and Families doctors Tashkent. Of these, there are 21 men, 39 women. At the age of 30 – 40 years – 20 patients, 41-50 years – 21 patients, 51-60 years – 15 patients and 61 and above years – 4 patients. The patients were divided into 2 groups : The main group of 30 patients who underwent surgery using a surgical treatment method developed by us. A control group of 30 patients who underwent traditional methods of surgical treatment. We studied the results of treatment before and after surgical treatment. Before treatment in both groups, there were no excellent and good results, satisfactory in the main group was 33.5%, in the control group 25%, after treatment 12 months. the main group had excellent and good results 87%, the control group 77%, improvement in treatment results shows the effectiveness of this treatment method.
Keywords: Carpal canal stenosis; surgical treatment; degree of disease